How is the concept of charisma used in the academic literature about biodiversity conservation? A systematic map protocol - Maxim Isaac; Caroline S. Fukushima; Biljana Macura; Enrico Di Minin; Ricardo A. Correia (Environmental Evidence)
Abstract Background The extinction of species is a multifaceted phenomenon shaped by the complex interplay between biological and socio-cultural factors. Public and academic preferences for different species often play a direct or indirect role in influencing the conservation outlook of these species. The “charisma” of species and other components of biodiversity is often mentioned as an important factor in shaping human preferences, determining both the scope of scientific studies and justifications for such scope. Here, we present a protocol for systematically mapping the use of the concept of “charisma” in relation to biodiversity peer-reviewed academic literature focused on biodiversity conservation. Methods The search targeting academic peer-reviewed research articles and reviews will be conducted in three publication databases, The Lens, Scopus and Web of Science (Core Collection and SciELO), and will be supplemented by search engine results from Google Scholar. Broad-scope searches will be performed in 3 different languages (English, Portuguese, and Spanish) and article screening will be performed at two stages to ensure the relevance of each entry and consistency amongst reviewers in their use of the defined inclusion criteria. The resulting systematic map of the literature will be summarised by employing a narrative synthesis approach, and through descriptive statistics and analysis of temporal trends.